2017
DOI: 10.18632/oncotarget.23807
|View full text |Cite
|
Sign up to set email alerts
|

Intrahepatic cholangiocarcinoma in the setting of HBV-related cirrhosis: Differentiation with hepatocellular carcinoma by using Intravoxel incoherent motion diffusion-weighted MR imaging

Abstract: Accurate preoperative differentiation of intrahepatic cholangiocarcinoma (ICC) and hepatocellular carcinoma (HCC) in the setting of cirrhotic liver is of great clinical significance because the treatment and prognosis of these entities differ markedly. Through a retrospectively research, we sought to determine the diagnostic performances of intravoxel incoherent motion (IVIM) and diffusion weighted imaging (DWI) parameters in the differentiating of ICC and HCC. According to the results, we found that apparent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
(38 reference statements)
2
17
1
Order By: Relevance
“…Data obtained from our study found significant differences among some of the IVIM-DWI parameters, including ADC, D slow , and D fast between HCC and ICC. The ADC and D slow of HCC tissues were obviously lower than those of ICC tissues, which is consistent with the results reported by Choi 17 and Wei et al 38 . The D fast value of HCC tissues was significantly higher than that of ICC tissues, which may be associated with the rich blood supply inherent to HCC, while the blood supply of ICC is poor 39 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Data obtained from our study found significant differences among some of the IVIM-DWI parameters, including ADC, D slow , and D fast between HCC and ICC. The ADC and D slow of HCC tissues were obviously lower than those of ICC tissues, which is consistent with the results reported by Choi 17 and Wei et al 38 . The D fast value of HCC tissues was significantly higher than that of ICC tissues, which may be associated with the rich blood supply inherent to HCC, while the blood supply of ICC is poor 39 .…”
Section: Discussionsupporting
confidence: 92%
“…The D fast value of HCC tissues was significantly higher than that of ICC tissues, which may be associated with the rich blood supply inherent to HCC, while the blood supply of ICC is poor 39 . This result was not observed by Wei et al 38 . The differential efficacy of D fast for malignant hepatic nodules with different pathological features is higher than those of the ADC and D slow , suggesting that D fast can better reflect the changes in the tissue microstructure compared to the ADC and D slow .…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…This phenomenon would be attributable to the changes in circulatory patterns due to portal hypertension, but there is limited information available on these possible changes in the literature. One way to differentiate between HBV-positive ICCs and HCCs is the use of apparent diffusion coefficient (ADC) derived from a mono-exponential model using diffusion weighted imaging (DWI) in MRI, but this method requires specific DWI imaging and is subject to further validation (68). Further research is needed to understand more on distinct radiological patterns on ICC tumours under the influence of HBV infection and cirrhosis.…”
Section: Discussion Discussionmentioning
confidence: 99%